PHILOSOPHICAL FOUNDATIONS OF THE SPIRITUAL AND MORAL DIMENSION OF SOCIO-ECOLOGICAL WELL-BEING (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article analyzes the spiritual and moral foundations of socio-ecological wellbeing in the context of contemporary environmental transformations. It examines the relationship between moral values, cultural norms, and social practices that shape the interaction between society and nature, with an emphasis on the Kyrgyz ethnoecological tradition. It demonstrates that the environmental values of responsibility, moderation, harmony, and solidarity act as collective regulators of environmental relations. It concludes that it is necessary to integrate these values with modern sustainable development strategies.
Keywords: socio-ecological well-being, spirituality, morality, ethnoecology, sustainable development, «National Spirit – Global Heights» Doctrine, environmental values.